Sistem Pemantauan Daya Listrik Berbasis Website - Lestari, Megi; Irwan, Irwan; Riezky Pratiwi, Indah (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Human life today is very dependent on electrical energy. In almost everyday life, people need electricity, whether in offices, households, education, industry, and others. Excessive use of electricity can cause waste both in terms of costs and energy itself. Careful monitoring is needed to find out how much electrical power is used in electronic equipment. The important thing for users to pay attention to is monitoring electrical power consumption so that the use of electronic equipment remains within the time and cost limits that have been previously set. Therefore, the aim of this research is to make it easier for users to carry out this monitoring through a website-based system. Data from the PZEM-004T sensor is processed by the ESP32 microcontroller, then sent to the database via the internet network. In this way, this information can be accessed by users anytime and anywhere via websites connected to the internet. The level of data accuracy on the website reaches 100%, according to the reading results from ESP32 and Power Quality Analyzer as a comparison.